2011
DOI: 10.1016/j.anr.2011.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Construct Equivalence and Latent Means Analysis of Health Behaviors Between Male and Female Middle School Students

Abstract: Health providers should consider gender differences when they develop and deliver health promotion programs aimed at adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Additionally, latent mean analysis (LMA) was performed to examine the difference of resilience by age, gender, and severity of disease ( 17 , 37 , 38 ). Although the difference between groups is often examined via the t -test or multivariate analysis of variance (MANOVA), these analyses may result in incorrect outcomes as they use measured variables that contain measurement errors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, latent mean analysis (LMA) was performed to examine the difference of resilience by age, gender, and severity of disease ( 17 , 37 , 38 ). Although the difference between groups is often examined via the t -test or multivariate analysis of variance (MANOVA), these analyses may result in incorrect outcomes as they use measured variables that contain measurement errors.…”
Section: Methodsmentioning
confidence: 99%
“…LAM controls for measurement errors to overcome the limitations of the t -test or MANOVA and to detect group differences in greater accuracy ( 37 ). To conduct LMA, the assumptions should be satisfied by the invariance test, that is, configural invariance, metric invariance, and scala invariance ( 37 , 38 ). Configural invariance examines whether identical latent variables are loaded between groups so as to confirm identical basic structures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As sample characteristics can be diverse and include various ages, cultures, genders and social groups, Park et al [7] suggested that researchers should account for group differences in measurement selection in order to prevent potential confounders that may lead to flawed conclusions. Therefore, it is desirable to conduct CFA in cases where data from specific populations have not undergone instrument reliability and validity testing [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in Northern Ireland, Kidscreen-27 has only been tested online using exploratory factor analysis methods [15]. Researchers [4, 7, 8] propose that psychometric models should be tested in multiple populations to determine whether the hypothesised structure is generalisable. Hence, it is necessary to conduct CFA on Kidscreen-27 to determine whether: (a) researchers should opt for the hypothesised 5-factor [11] or modified [14] 7-factor structure; and (b) whether Kidscreen-27 is a psychometrically consistent measure of HRQOL for children of low SES across both Irish jurisdictions (Northern and Republic).…”
Section: Introductionmentioning
confidence: 99%